An Analysis of Students Listening Ability in Recognize English Homophones - Nabila Sadida; Otong setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Listening ability is an essential skill in learning English and plays an important role in daily communication, especially in understanding spoken messages. However, many students still experience difficulties in listening comprehension, particularly in recognizing and distinguishing homophones. This study aims to analyze and describe the listening ability of third-semester students of class 3B, English Education Department, UIN Sunan Gunung Djati Bandung, in identifying English homophones. It also examines which homophones most frequently cause errors and identifies the factors influencing these difficulties, as well as the instructional implications.This research employed a qualitative descriptive approach. The data were collected through a homophone listening test consisting of ten multiple-choice questions and five essay questions. The findings reveal that students’ ability to recognize homophones varies. Homophones with high phonological similarity tend to cause more errors, especially when they are presented without sufficient contextual support. In addition, factors such as speech rate, speaker accent, cognitive load, and limited listening practice contribute to students’ difficulties in understanding homophones. These findings highlight the importance of implementing more contextual and structured listening instruction to help students better understand and distinguish homophones.